2016
DOI: 10.1097/brs.0000000000001590
|View full text |Cite
|
Sign up to set email alerts
|

Reoperation Rates After Anterior Cervical Discectomy and Fusion for Cervical Spondylotic Radiculopathy and Myelopathy

Abstract: 3.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 21 publications
0
22
0
Order By: Relevance
“…12 According to our findings, smoking and diabetes have been previously identified as important risk factors for cervical radiculopathy, perioperative complication rates, and worse postoperative outcome. 1,10,14,21,22 In this cohort of painless paresis, we found C-5 and C-6 to be the most frequently affected nerve roots. Anatomically, the focal compression at the entrance of the neural foramen was most often attributable to uncovertebral joint arthrosis with or without soft-tissue pathologies and led to a predominant isolated lesion of the motor ventral nerve root.…”
Section: Discussionmentioning
confidence: 51%
“…12 According to our findings, smoking and diabetes have been previously identified as important risk factors for cervical radiculopathy, perioperative complication rates, and worse postoperative outcome. 1,10,14,21,22 In this cohort of painless paresis, we found C-5 and C-6 to be the most frequently affected nerve roots. Anatomically, the focal compression at the entrance of the neural foramen was most often attributable to uncovertebral joint arthrosis with or without soft-tissue pathologies and led to a predominant isolated lesion of the motor ventral nerve root.…”
Section: Discussionmentioning
confidence: 51%
“…ACDF is widely used to treat multilevel CDDD [22]. However, several studies reported that ACDF could result in certain complications [9,[23][24][25][26][27][28]. It has been reported that the incidences of complications in different levels of fusion are variable: the rates of internal fixation failures in one to four-level fusion are 20%, 36%, 71%, and 80%, respectively [23]; the incidences of reoperation in one to four-level fusion are 5.8%, 6.5%, 8%, and 16.8%, respectively [27]; in addition, the incidences of ASD in single-level fusion and multilevel fusion are 13.2% and 32.1%, respectively [29].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have discovered higher rates of reoperation for myelopathy compared with radiculopathy, 9 , 23 which may reflect differences in the number of vertebral levels operated. The risk of reoperation has been found to be smaller in longer fusions.…”
Section: Discussionmentioning
confidence: 95%